Targeting intracellular mediators of pattern-recognition receptor signalling to adjuvant vaccination - Wales, J; Andreakos, E; Feldmann, M; Foxwell, B (2007)
PRR (pattern-recognition receptor) signalling is involved early in the immune response and therefore would be attractive to target during vaccination. The use of PRR ligands has shown some success; however, toxicity and non-specificity are issues with this strategy. The targeting of PRR intracellular signalling networks would allow for greater specificity and reduced systemic toxicity. The present review examines the successes seen with overexpression or repression of PRR signalling molecules. ©The Authors.